PERSEPSI MAHASISWA KEPERAWATAN TENTANG PELAKSANAAN SIMULASI PENANGGULANGAN BENCANA - Rizki Wan Oktabina; Joice Mermy Laoh; Nuswatul Khaira (Journal Keperawatan, 2023)
Nurses are the health profession with the most number when compared to other health professions. They play a critical role in disaster management. Competencies related to disaster management are acquired by nurses during their learning process in higher education institutions. One of the challenges in nursing education is the application of theoretical knowledge into practice, particularly in disaster situations. A learning model that can integrate nursing theory with practical skills is simulation-based learning. This research aims to evaluate students' perceptions regarding the implementation of disaster management simulations in the Nursing Disaster course at the Nursing Diploma III Program in Banda Aceh. The respondents of this study were 48 students of the Diploma Three Nursing Program in Banda Aceh. Data collection was carried out through a Likert-scale questionnaire containing questions about students' perceptions of various aspects of simulation implementation. The results of this research indicate that, overall, students' perceptions of the implementation of disaster management simulations in the Nursing Disaster course are very positive.